(untitled) (International relations and international law Journal, 2016)
This article devoted to the investments to digital technologies. Because the economy is rapidly covers into the virtual world, and today 14% of global commerce accounted on online . Business has become digital, and technology – the basis for creating customer value and income. A success in the digital world is mainly determined by the efficiency of information technology and the priorities of the unit . Particular attention is paid to that successful in the digital world countries set a goal – to improve the means of communication and technology, investing in this sector, more investment. At the same time, and the Republic of Kazakhstan as well as all other countries, focuses on attracting investment to digital technology, developing long-term strategies, creating departments, aimed at developing the domestic information technology industry . This article describes how to develop projects for investment in technological industries in Kazakhstan: development of a new generation of television, the development of the telecommunications market and mobile communications, the development of digital marketing.Inflows of foreign direct investment is very useful for the qualitative transformation of the economy and the rise of technological capacity, and to stabilize the exchange rate. The development of these tech industries at the expense of the Program on development of information and communication technologies in the Republic of Kazakhstan for 2010 – 2014 years.The article also says that at the moment the world held various conferences and forums dedicated to information technology. And an example of the forum took place in Turkey – Webit Congress 2013.